Konstruksi Pemberitaan Backpack Journalist Di Media Sosial - Sisca T. Gurning (Jurnal Ilmu Komunikasi, 2022)
The development of internet technology opens up opportunities for the development of citizen journalism. This study discusses how the construction of news of the backpack journalist “Expedition Indonesia Biru” on social media. The purpose of this study is to find out the construction of news carried out by citizen journalists with the concept of the blue Indonesian expedition of backpack journalist in their documentary film on the YouTube channel. The research method used is the semiotic analysis of Roland Barthes. The results of the research show that there is news construction by backpack journalists against the feud of the Samin people and the cement factory. It is unavoidable that the news is only seen from one point of view of the Samin people, so that the reporting is not balanced. There is denial of journalistic ideology, where a journalist must be disciplined in verifying, comprehensively, proportionally, and maintain independence from news sources. This element of journalism cannot be carried out by backpack journalists because they do not represent certain media institutions.